Procedural Sedation in Children for Magnetic Resonance Imaging-Comparison between Ketamine Diazepam Combination with Midazolam Fentanyl Combination - Maruf, AA; Hossain, MD; Ahmed, M; Samsad, IA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):60-65. The abstract of this article is available on the PubMed website